CALCIUM-DEPENDENT PROTEIN KINASE 32-mediated phosphorylation is essential for the ammonium transport activity of AMT1;1 in Arabidopsis roots. (23rd May 2020) - Qin, De-Bin; Liu, Meng-Yuan; Yuan, Lixing; Zhu, Yun; Li, Xi-Dong; Chen, Li-Mei; Wang, Yi; Chen, Yi-Fang; Wu, Wei-Hua; Wang, Yang
Abstract : CALCIUM-DEPENDENT PROTEIN KINASE 32 acts as a positive regulator of ammonium uptake in roots by phosphorylating AMMONIUM TRANSPORTER 1;1 to promote its opening. Abstract: Protein kinase-mediated phosphorylation modulates the absorption of many nutrients in plants. CALCIUM-DEPENDENT PROTEIN KINASES (CPKs) are key players in plant signaling to translate calcium signals into diverse physiological responses. However, the regulatory role of CPKs in ammonium uptake remains largely unknown. Here, using methylammonium (MeA) toxicity screening, CPK32 was identified as a positive regulator of ammonium uptake in roots. CPK32 specifically interacted with AMMONIUM TRANSPORTER 1;1 (AMT1;1) and phosphorylated AMT1;1 at the non-conserved serine residue Ser450 in the C-terminal domain. Functional analysis in Xenopus oocytes showed that co-expression of CPK32 and AMT1;1 significantly enhanced the AMT1;1-mediated inward ammonium currents. In transgenic plants, the phosphomimic variant AMT1;1 S450E, but not the non-phosphorylatable variant AMT1;1 S450A, fully complemented the MeA insensitivity and restored high-affinity 15 NH4 + uptake in both amt1;1 and cpk32 mutants. Moreover, in the CPK32 knockout background, AMT1;1 lost its ammonium transport activity entirely. These results indicate that CPK32 is a crucial positive regulator of ammonium uptake in roots and the ammonium transport activity of AMT1;1 is dependent on CPK32-mediated phosphorylation.